Sinistroporomonorchis bolini n. sp. (Trematoda: Monorchiidae) from the Ocellated killifish, Floridichthys polyommus (Cyprinodontidae) in the Yucatán Peninsula, Mexico based on an integrative taxonomy analysis - Leopoldo Andrade-Gómez; Juan F. Espínola-Novelo; Brenda Solórzano-García; Gerardo Pérez-Ponce de León (Parasitology)
Members of Sinistroporomonorchis Wee, Cutmore, Pérez-del-Olmo & Cribb, 2020 represent a small group of trematodes belonging to the Monorchiidae Odhner, 1911 with 5 species described from mugilid hosts. Specimens consistent with the generic concept of Sinistroporomonorchis were obtained from Floridichthys polyommus (Cyprinodontidae); most of them were juveniles from 4 localities within the Yucatán Peninsula. After a detailed morphological examination including scanning electron microscopy images and a principal component analysis, the specimens collected represented a new species, Sinistroporomonorchis bolini n. sp. The new species can be differentiated by the presence of an overall large pharynx including the proportion of pharynx width to oral sucker width, a uterus arranged in 2 main lateral fields, and by presenting robust caeca. In addition, sequences of the 28S of large subunit of nuclear ribosomal RNA and cox1 of the mitochondrial DNA were obtained. Phylogenetic trees inferred from each dataset, placed all the specimens in a monophyletic clade, confirming that the isolates belonged to the same species. The new species is the sixth described for the genus Sinistroporomonorchis, the fifth described from the Yucatán Peninsula and the first described from a non-mugilid host.